Perceived Roles of Skills in Growth and Transformation of Ready Made Garments and Pharmaceutical Industries in Bangladesh: Results from an Industry Survey - Kalam, Md. Abul; Shimu, Sheikh Shahana (Asian Journal of Education and Training, 2020)
This article examines the contribution of Technical and Vocational Education and Training (TVET) programs to growth and transformation in the Ready Made Garments (RMG) and Pharmaceutical industries in Bangladesh as perceived by the industries through a company survey with 100 RMG and 61 Pharmaceuticals. It identifies a missing link between skill development through TVET and the needs of industry in Bangladesh. Results show that, with the exception of pre-employment TVET for technicians and higher management, on average less than 20% of the companies had workers with pre- and in-employment TVET across all occupational levels. This indicates that TVET providers better fulfil the needs of industry for a smaller number of employees at mid- and higher management level compared to TVET for large numbers of employees at lower levels of general workers, operators and supervisors. It concludes that establishing strong collaboration and partnerships between government, industry and TVET institutions is necessary to harness human resources for employment and development through the world of work.